Management of the services of emergency department in a specialized hospital a cross sectional study (Update Dental College Journal, 2016)
Emergency department is one of the most important part of the hospital and also vulnerable to criticism. The reputation of a hospital rests to a large extent on the service of emergency department. A descriptive type of cross sectional study was conducted at Emergency Department (ED) of National Institute of Cardiovascular Diseases Hospital (NICVD), Dhaka to assess different aspects of the service management of ED which includes opinion regarding different services, reception facilities, overall management of ED, waiting time for the patients to be attended by a doctor, required time for completion of emergency treatment, suggestions of service receivers for further improvement of ED of the hospital. A total of 121 patients or patient attendance and 39 health personnel were interviewed by a structured questionnaire and a checklist was utilized for availability of equipments and drugs in ED. The collected data were processed and analyzed meticulously with the help of SPSS (Version 21) software on the basis of different variables. According to Standard Operating Procedure (SOP) all instruments were present, 15 emergency drugs had been listed, out of them Inj. Streptokinase, antiseptic liquid were not available at that time in the ED of the hospital. The study revealed that out of 160 respondents the mean age was 40.3 ± 5.81 years, opinion about different services provided in ED more than two third found satisfied, only 18.1 % service receivers mentioned about the waiting time at ED to be seen by a doctor was ?3 minutes, more than half (54.5 %) required 20-30 minutes for completion of emergency treatment, different suggestions were suggested for further improvement of ED like increase number of wheel chair, stretcher, ambulance, to supply required medicine from the hospital, separate ECG room for female patients, waiting room for patients attendance etc. However, specific problems identified by different stakeholders need to be critically appraised by the authority to improve the services further.Update Dent. Coll. j: 2016; 6 (1): 15-20